CELL-WALL FRACTIONS FROM PARACOCCIDIOIDES-BRASILIENSIS INDUCE HYPERGAMMAGLOBULINEMIA - Deoliveira, S. L.; Dasilva, M. F.; Soares, AMVD; Silva, C. L. (Springer, 1993)
The antibody response against the antigen sheep red blood cells (SRBC) was investigated in mice pre-treated with formalin-killed Paracoccidioides brasiliensis or with cell wall fractions of the fungus. Pre-treatment with P. brasiliensis, as well as with the F1 fraction and beta-glucan significantly increased the anti-SRBC antibody response in the experimental groups as compared to the control group that received only SRBC. This immunomodulatory effect varied with the different doses employed and with pre-treatment time. We conclude that the cell wall fractions of P. brasiliensis might play an important role in the hypergammaglobulinemia associated with Paracoccidioidomycosis.
Keywords: BETA-GLUCAN; CELL WALL; HYPERGAMMAGLOBULINEMIA; PARACOCCIDIOIDOMYCOSIS; PARACOCCIDIOIDES-BRASILIENSIS